Leptospirose em pacientes negativos à dengue, Estado de São Paulo, Brasil - Fornazari, F.; Richini-Pereira, V. B.; Joaquim, S. F.; Langoni, H. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is one of the most important zoonosis worldwide. In humans, it is considered a neglected disease, mainly because of their non-specific symptoms and the increased attention of public health authorities to other diseases with similar clinical presentation, especially dengue.